c - Pundyk, Grace (Singapore : Times Editions, 2003)
From the Orang Asli and other indigenous peoples to the non- bumiputera Chinese and Indians - Malaysia is a country of many different cultures and ethnic groups. Join this voyage of discovery and take a closer look at the lives of the Malaysians and the land of longhouses, leatherbacks, rafflesia and the Ranjang River
Includes bibliographical references and index
Keywords: Malaysia -- Juvenile literature